A powerful vision: power affects visual search behavior - Guinote,Ana (2009)
Preliminary studies indicate that being in a powerful or powerless position affects the individual’s ability to focus on task relevant information. In the present study, we examined which components of attention are affected by power using visual search paradigms. In three studies, participants were first primed with power or powerless, and then performed visual search tasks. In these tasks the contribution of top-down and bottom-up attentional guidance was manipulated by altering either the physical or semantic similarity between target and distracters. The results indicated that social power affects the speed of visual search. Furthermore, these effects derived from differences in top-down, but not bottom-up, components of attention, and occurred both when targets were discriminated on the basis of perceptual as well as of semantic properties.